1989
DOI: 10.1111/j.1600-0714.1989.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of human papillomavirus (HPV) DNA in focal epithelial hyperplasia

Abstract: Five focal epithelial hyperplasia (FEH) specimens from four patients were examined by Southern blot hybridization analysis to determine the specific human papillomavirus (HPV) types present. The histomorphologic features of these specimens were also evaluated and a broad variety of changes including koilocytes, mitosoid cells, ballooning cells and cells showing individual cell keratinization were noted. FEH lesions from the three patients sharing a familial relationship demonstrated HPV DNA sequences that were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1
4

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 32 publications
2
23
1
4
Order By: Relevance
“…Described formally in 1965 in Native-Americans by Heck [1], this pathology is frequent in populations of 2-13 years of age, and its incidence is unequally distributed worldwide, affecting Native-Americans and indigenous populations the most [1][2][3][4][5][6]. There is no concrete evidence of affection of a particular male or female gender, as this varies with previous studies [7].…”
Section: Introductioncontrasting
confidence: 54%
“…Described formally in 1965 in Native-Americans by Heck [1], this pathology is frequent in populations of 2-13 years of age, and its incidence is unequally distributed worldwide, affecting Native-Americans and indigenous populations the most [1][2][3][4][5][6]. There is no concrete evidence of affection of a particular male or female gender, as this varies with previous studies [7].…”
Section: Introductioncontrasting
confidence: 54%
“…A viral etiology has been evidenced by several immunocytochemical and in situ hybridization studies that have identified the presence of human papillomavirus (HPV) subtypes 13 and 32. Human papillomavirus subtypes 1, 6, 11 and 55 have also been implicated [3,12,[24][25][26][27][28]. It has been postulated that an infection with these viruses leads to irreversible cellular degeneration and affects the expression of cytokines 14, 15, 16 and 19, which is thought to result in an alteration in cytokeratin immune reactivity and may modify the metabolic pattern of epithelial cytokeratins [3].…”
Section: Discussionmentioning
confidence: 99%
“…Les facteurs qui déter-minent la susceptibilité pour l'HEF et sa transmission sont encore mal connus, mais cette affection touche de préfé-rence certains groupes ethniques ; la présence de plus d'un cas d'HEF dans une même famille suggère qu'une prédisposi-tion génétique intervient dans la pathogénie de cette maladie [5][6][7][13][14][15][16]. Un facteur génétique présent dans certaines ethnies (esquimaux, amérindiens, turcs, nord-africains.…”
Section: Discussionunclassified